2017
DOI: 10.1088/1748-9326/aa6056
|View full text |Cite
|
Sign up to set email alerts
|

Large scale land acquisitions and REDD+: a synthesis of conflicts and opportunities

Abstract: Large scale land acquisitions (LSLA), and Reducing Emissions from Deforestation and forest Degradation (REDDþ) are both land based phenomena which when occurring in the same area, can compete with each other for land. A quantitative analysis of country characteristics revealed that land available for agriculture, accessibility, and political stability are key explanatory factors for a country being targeted for LSLA. Surprisingly LSLA occur in countries with lower accessibility. Countries with good land availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…most common intended land uses of global LSLA is for agriculture and secondarily for forestry, of which 59% and 17% are for transnational deals and 58% and 23% for domestic deals, respectively. Land grabbing flows from the global South to the North and from the South to the South have been characterized in previous studies , Seaquist et al 2014, Carter et al 2017. Yet, we further reveal that domestic and transnational land acquisitions driven by investors in low and low middle income countries also make up a substantial proportion.…”
Section: Conclusion and Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…most common intended land uses of global LSLA is for agriculture and secondarily for forestry, of which 59% and 17% are for transnational deals and 58% and 23% for domestic deals, respectively. Land grabbing flows from the global South to the North and from the South to the South have been characterized in previous studies , Seaquist et al 2014, Carter et al 2017. Yet, we further reveal that domestic and transnational land acquisitions driven by investors in low and low middle income countries also make up a substantial proportion.…”
Section: Conclusion and Discussionsupporting
confidence: 60%
“…In this study, we extend this research and show that global LSLA networks are mainly characterized by dominant land grabbing flows from the developing to the developed world (75.4%), with small percentages of land grabbing flows contained within the developing world (22.8%) or the developed world (1.8%). Land available for agriculture and accessibility were identified as key factors for counties being targeted for transnational LSLA (Carter et al 2017), and Nolte et al (2016) reported that globally most LSLA deals (∼80%) are for agriculture. When considering all concluded and intended land deals (and after excluding failed ones), we also find that the Abbreviation note.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving towards alternative approaches to sciencepolicy interactions, such as co-production (Mauser et al 2013), could increase the relevance and usability of land-use science for society and decision-making. With respect to global land governance, new emerging processes such as large-scale land acquisition or spilloff and offsite effects (Seppelt et al 2011, Carter et al 2017, Pascual et al 2017 pose challenges to land management which is mostly implemented through law, rule or incentives at the local to regional scale. Surprisingly, large-scale land acquisitions are not an issue in global-scale agro-economic models (Debonne et al 2018).…”
Section: Outlook: Guiding Questions Of the Emerging Topicsmentioning
confidence: 99%